Investigation of rehydration kinetics of open-sun dried carrot slices - Ismail, Osman (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2017)
In this study, rehydration kinetics at 25 ve 50(omicron)C of under open-sun dried carrot (Daucus carota L.) slices which are untreated and treated were investigated. By the obtained data, parameters related to rehydration kinetics and diffusion mechanism was calculated. The rehydration experiments, maximum equilibrium rehydration values were achieved with the naturally dried carrot slices. For the naturally dried carrot slices, experimental equilibrium rehydration (R-eq), theoretical equilibrium rehydration (R-max) and diffusion coefficient (D) at 50(omicron)C were calculated as 5.73 (g(water)/g(dry) (matter)), 5.96 (g(water)/g(dry) (matter)) and 2.15x10(-10) m(2)/s, respectively. Rehydration exponent value (n), which is also important to identify the dried carrot slices diffusion type, was determined at between 0.331 - 0.367 Because of the exponent value less than 0.50, diffusion process was defined as natural Fickian diffusion.
Keywords: Carrot; pre-treatment; dehydration; rehydration; diffusion; SOAKING; SYSTEMS; LEAVES; GRAIN; Engineering